Analysis of Anionic Surfactant Concentration and Temperature Effect on Surfactant and Oil Flow Time in Capillary Pipe (Laboratory Study) - HENDANI HAQIQI (NIM 12204033); Pembimbing: Dr. Ir. Leksono Mucharam, IRCHAM
Surfactant is known as an active material which could lower interfacial surface tension between oil and water. Surfactants are widely use in EOR (Enhanced Oil Recovery) operation to increase oil recovery factor by injected to the reservoir so that we can produce oil trapped in rock pores. There is several physical properties in capillary pores rock system such as capillary pressure, wettability, interfacial tension, and fluids viscosity, which can give influence to fluid flow in reservoir.This physical properties are influent by temperature change, pore radius, and also type of flowing fluid. This properties change may be detected from the flow time of fluids in that capillary medium. This paper investigates the effect of local anionic surfactant concentration and temperature change to the flow time of surfactant and oil in capillary pipe, which is can represent the real situation in reservoir rock. Theoritically, increasing concentration of surfactant will decrease the flow time of surfactant solution because of the ability of surfactant to influence the properties of interfacial tension. From experiment, the result showed that surfactant solution has an optimum concentration, which has the shortes flowtime. This study also showed that increasing surfactant concentration may alter the wettability of glass-pipe surface.